High Temperature Exposure Assessment of Graphene Oxide Reinforced Cement - Yan, Jianwei; Wang, Jiankang; Chen, Hengyi; Xiang, Ping (Frontiers in Materials, 2022)
This study aims to carry out a high-temperature exposure assessment for graphene oxide (GO) reinforced cement in terms of weight loss, flexural strength, and compressive strength. Different additive amounts of GO in cement are experimentally studied to unfold its effect on enhancing the mechanical performance of prepared GO reinforced cement. Temperatures are chosen as room temperature, 200, 400, 600, and 800°C, corresponding to different reaction status of cement. It is found that as the temperature increases, the water evaporates from the GO reinforced cement. Evaporated quantity of water relies on the reaction status, and the relation between weight loss and temperature is provided. Benefiting from the bonding effects of GO, hydrated calcium silicate hydrate (C–S–H) is chemically produced and, thus, a reticular bridging system, which is greatly helpful to enhance the flexural strength, is formed. Unlike flexural strength, adding GO into cement statistically has little effect on the compressive strength, except when the temperature rises up to 800°C due to the occurrence of decarburization from dehydration.